DIGITAL TRANSFORMATION OF TOURISM VILLAGES: IMPLEMENTATION OF MOBILE APPLICATIONS AND E-PESESSERTOUR WEBSITES FOR PROMOTION OF LEMBUNG MARINE TOURISM - Darmawan, Aang; Hadi, Saiful; Muqaddas, Zaiful; Daryanto, Eko; Tri Wahyurini, Endang; Ariyanto, Fathorrozi; Ferdiansyah, Doni (Yayasan Education and Social Center, 2025)
The potential of marine tourism, especially mangrove ecotourism, in Lembung Village, Pamekasan, has not been optimally promoted due to the limitations of conventional methods and minimal use of digital channels. This condition hinders the visibility and attractiveness of destinations in the digital era. This community service aims to initiate a digital transformation of Lembung Village tourism promotion by developing and implementing an integrated platform (mobile application and website) e-PesesserTour. The implementation method is participatory, involving local partners (Pokdarwis, BUMDes) in needs analysis, design, development, and implementation of the platform. The primary focus of implementation is increasing partner capacity through workshops and intensive mentoring in digital marketing strategies, content creation, and management of the e-PesesserTour platform (https://e-lembung-pesessertour.com) as a promotional tool. The results show the success of launching a functional, informative digital promotion platform that displays the village's attractions, including 3 new tour packages that have been developed. There was a significant increase in the digital capacity of partners, as evidenced by 90% of participants stating an increase in understanding of digital technology and an average score of post-training knowledge/skills tests reaching 85%. During the program implementation period, positive impacts were also observed in the form of an increase in tourist visits of up to 40%, an increase in BUMDes income of up to 50%, and a level of tourist satisfaction reaching 85%, some of which can be attributed to the rise in the quality of digital promotion and services. It was concluded that implementing the e-PesesserTour platform, supported by strengthening HR capacity, played a significant role as a catalyst for the digital transformation of Lembung Village tourism promotion, increasing the visibility and competitiveness of the destination sustainably.